1996
DOI: 10.5860/crl_57_03_234
|View full text |Cite
|
Sign up to set email alerts
|

A Reputational Study of Academic Publishers

Abstract: In both selecting individual titles and designing gathering plans, collection d~velopment librarians are strongly influenced by the perceptions they have about publishers. In the near absence of data that might indicate the overall perceptions the collection development community has about academic publishers, the authors distributed a reputational assessment survey to a national sample of heads of collection development in academic libraries. The resulting data on perceptions of the quality and academic relev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 3 publications
0
10
0
Order By: Relevance
“…Libcitations should also correlate with quality rankings of the presses that publish academic books (Metz & Stemmer 1996;Goodson et al 1999;Lewis 2000;Wiberley 2002Wiberley , 2004. Similar quality rankings of academic journals (East 2006;Mingers & Harzing 2007;Haddow 2008) have proved controversial (see, e.g., Corbyn 2008a.…”
Section: Discussionmentioning
confidence: 99%
“…Libcitations should also correlate with quality rankings of the presses that publish academic books (Metz & Stemmer 1996;Goodson et al 1999;Lewis 2000;Wiberley 2002Wiberley , 2004. Similar quality rankings of academic journals (East 2006;Mingers & Harzing 2007;Haddow 2008) have proved controversial (see, e.g., Corbyn 2008a.…”
Section: Discussionmentioning
confidence: 99%
“…They found that collection development librarians held university presses in high regard, with librarians in their sample consistently ranking university presses at the top in terms of familiarity, relevance, and quality. 7 Other studies have examined measures of circulation and reached similar conclusions: scholars in humanities fields use items published by university presses regularly. One study focusing on usage of resources in the humanities categorized patron materials requests by publisher.…”
mentioning
confidence: 96%
“…Metz and Stemmer (1996), for example, surveyed collection development officers in academic libraries about the prestige of different publishers, with university presses being found to be highly regarded. They believed that subject differences, the existence of specialised publishers and the necessarily subjective nature of judgements were all problems for assessing publishers.…”
Section: Publisher Prestigementioning
confidence: 99%